Agrobacterium tumefaciens‐mediated transformation for targeted disruption and over expression of genes in the poplar pathogen Sphaerulina musiva. Issue 3 (13th January 2014) - Foster, A. J.; Morency, M. J.; Séguin, A.; Tanguay, P.; Balci, Y.
Summary Sphaerulina musiva causes both leaf spots and cankers on poplar. Leaf spots can lead to defoliation and cankers on branches and primary stems can lead to stem breakage and tree mortality. The recent availability of both the S. musiva and Populus trichocarpa genomes offers a great opportunity to study host–pathogen interactions. To better understand the factors involved in S. musiva pathology, we present a strategy for the transformation of this species using Agrobacterium tumefaciens. Binary plasmids were generated with hygromycin B phosphotransferase (hph) flanked by upstream and downstream sequences of polyketide synthase‐like (PKS‐L1) gene to generate targeted gene disruptants by homologous recombination. Plasmids were also constructed for constitutive expression reporter genes eGFP and mCherry to help with histological characterization of the pathogen during infection. Gene knockouts were identified by PCR and confirmed by sequencing and Southern blotting. No significant differences were observed in melanin production between PKS‐L1 disruptants and wild type isolates. Colonies expressing reporter genes were identified by fluorescent stereomicroscopy. This method is a promising tool for the characterization of pathogen genes through reverse and forward genetics and for introducing markers for histopathological study.